2004
DOI: 10.1038/sj.bjc.6601684
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Id-1 is significantly associated with tumour angiogenesis in human pancreas cancers

Abstract: It has been suggested that Id-1 has a critical role in the tumour progression and aggressiveness of several human cancers. However, the clinicopathological and biological significance of Id-1 overexpression remains unclear in human primary cancer. To investigate the association between Id-1 expression and cell proliferation or tumour angiogenesis, we examined the cell cycle kinetic indices (the proliferation and apoptotic indices, PI and AI) and intratumoral microvessel density (MVD) in 65 human pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
2
36
1
4
Order By: Relevance
“…Another breast cancer study found a negative prognostic impact of increased ID1 expression . Similar results have been published regarding pancreatic cancer (Lee et al, 2004), cervical cancer (Schindl et al, 2001), and ovarian carcinomas . In these studies, stronger ID1 expression was consistently associated with poorly differentiated tumours and a more aggressive behaviour.…”
Section: Discussionsupporting
confidence: 78%
“…Another breast cancer study found a negative prognostic impact of increased ID1 expression . Similar results have been published regarding pancreatic cancer (Lee et al, 2004), cervical cancer (Schindl et al, 2001), and ovarian carcinomas . In these studies, stronger ID1 expression was consistently associated with poorly differentiated tumours and a more aggressive behaviour.…”
Section: Discussionsupporting
confidence: 78%
“…Overexpression of Id-1 in prostate cancer cells also promotes metastasis through increased angiogenesis and invasiveness (Coppe et al, 2004). Reduced expressions of Id-1 and Id-3 have been demonstrated to inhibit the metastatic ability of gastric cancer cells (Tsuchiya et al, 2005), and Id-1 expression has been shown to be associated with the presence of invasion in endometrial carcinoma (Takai et al, 2001) and tumour angiogenesis in human pancreatic cancer (Lee et al, 2004). In lines with these results, we found that primary ESCC at M1 stage had a significantly (P ¼ 0.012) higher nuclear expression of Id-1 than the M0 stage tumours.…”
Section: Discussionmentioning
confidence: 99%
“…ID1's proliferative and antiapoptotic functions have been correlated with the onset and progression of a variety of human tumors, including those of mammary gland and pancreas (28); indeed, its overexpression is significantly associated with increased tumor angiogenesis and worse prognosis in these cancers (3,33). It has been shown that ID1 was essential for the metastasis of cancers to the lung in mouse models of cancer (13,18).…”
Section: Discussionmentioning
confidence: 99%